PENINGKATAN EKONOMI DESA MELALUI WISATA ALAM - Irtifah, Irtifah; Ghufron, Moh Idil (Media Mahardhika, 2019)
A tour is industry influencing society economy and prospesity level. Creativity and innovation is necessary for the management and preservation of tour to keep existing andinviting more the tourist. The porpuse of this research is to analize development and rising level of village economy by observing the varietyof natural potential in the village, the development is done in stage by the porpuse to increase the amount of taurist, by the qualitative method, the data collection is by interviwing the tour manager. This research succeeds to prove the development and rising level of the village economy influenced by the level of village real income. It is different montly for about 3,4 million and the village is wonosari grujugan bondowoso. In brief, every village has a different potential. The thinking, skill and coperation of society with Indonesia forestry side to develop nature potential which has special caracteristic and the interest of lokal or international tourits